2012
DOI: 10.1063/1.4764053
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted resonant domain wall nucleation in permalloy nanowires

Abstract: We have designed a system to study microwave assisted domain wall nucleation in permalloy nanowires. We find a substantial decrease in the nucleation field when microwave fields are applied, in comparison to pulse fields. A clear resonance peak is observed in the frequency dependence of the nucleation field, which coincides with the uniform mode ferromagnetic resonance frequency. Owing to the well-defined nucleation process, the switching field distribution is small in contrast to previous reports. Our results… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Specific choices of the polarity and duration of the current pulses and polarity of magnetic fields led to stochastic pinning of DWs in the nanowire region bounded by the current lines as well as the injection of vortex and transverse walls into the nanowire. In the same year, Hayashi et al [58] used short lived current pulses (with ∼ns lifetimes) to decrease the magnetic fields required to nucleate DWs in IM nanowires. They found that the nucleation field reduced by around half and the distribution of the switching fields decreased in width as well and the authors attributed this to using localised fields generated by the current lines.…”
Section: Dw Nucleationmentioning
confidence: 99%
“…Specific choices of the polarity and duration of the current pulses and polarity of magnetic fields led to stochastic pinning of DWs in the nanowire region bounded by the current lines as well as the injection of vortex and transverse walls into the nanowire. In the same year, Hayashi et al [58] used short lived current pulses (with ∼ns lifetimes) to decrease the magnetic fields required to nucleate DWs in IM nanowires. They found that the nucleation field reduced by around half and the distribution of the switching fields decreased in width as well and the authors attributed this to using localised fields generated by the current lines.…”
Section: Dw Nucleationmentioning
confidence: 99%
“…Micromagnetic simulations have shown that, in 16 nm composite nanopillars, consisting of ferromagnetically coupled soft and hard magnetic sections, MAS can be realized even if the damping constant of the hard magnetic section is large [11]. Several works have focused on the MAS in nanowires [12][13][14] but mainly in the form of permalloy thin film strip waveguides. The wall structure and dynamic response to an applied field (wall velocity and Walker fields) in nanostrips depend sensitively on the geometrical characteristics, due to the demagnetizing field arising from the precessional magnetization component perpendicular to the strip plane [15].…”
Section: Introductionmentioning
confidence: 99%
“…A number of alternatives to the use of magnetic fields, including electric fields or microwave-assisted generation of DWs in patterned nanowires, have been investigated [14,15]. It has been shown that a Slonczewski-like spin torque assisted by an Oersted field allows controlled injection of a series of DWs, providing a controlled method for writing binary information [16].…”
Section: Introductionmentioning
confidence: 99%